Electrical conductivity, porosity and density of 12 gravity cores from RV MARIA S. MERIAN cruise MSM111 - Tilo von Dobeneck; Michal Kucera; Johan C Faust (PANGAEA, 2025)
All sediment series recovered during MERIAN Cruise MSM 111 by gravity coring were subject to routine electrical conductivity logging, which was performed on the closed full, and largely pore-water-saturated core segments. The electrical conductivity σs or resistivity Rs (=1/σs) of marine sediment is primarily determined by porosity, pore-water saturation, pore-water salinity, and temperature, while electrically conducting matrix components such as clays are of a minor relevance. The electrical conductivity σs was determined using an inductive non-contact sensor. The system applies high-frequency magnetic fields by a transmitter coil inducing electrical eddy currents in the sediment which are proportional to conductivity. Their secondary field is recorded and yields raw, calibrated and temperature-corrected (T=20°C) values for conductivity and resistivity. Porosity was calculated according to the empirical Archie extquotesingles equation Rs/Rw = k·φ^(-m) where the ratio of sediment resistivity Rs and pore water resistivity Rw can be approximated by a power function of porosity φ. Values of 1.30 and 1.45 were used for the constants k and m, respectively. The calculated porosity φ is subsequently converted to wet bulk density ρwet by ρwet = φ·ρf + (1 - φ)·ρm (with a pore water density ρf of 1030 kg/m3 and a matrix density ρm of 2670 kg/m3. The MARUM Multi-Sensor Core Logging System (MSCLS) is mounted with a commercial Geotek non-contact-resistivity (NCR) sensor. For the necessary NCR calibration a set of saline solutions at concentrations of 0.35 - 1.75 - 3.5 - 8.75 - 17.5 - 35 g/l was recorded daily. The resistivity sensor averages over approximately 12 cm core length. The core segment data were numerically corrected for (geometry-related) signal decay within the first and last 14 cm of each segment to ideally create seamless records. Nevertheless, conductivity data of the first and last 5 cm of each segment had to be discarded, as they usually showed artifacts of partial pore-water and/or sediment loss.